Penerapan Media Visual di Kelas 2 MI Baitul Makmur Kecamatan Bangsalsari Kabupaten Jember Tahun Pelajaran 2023/2024 sebagai Upaya Peningakatan Motivasi Belajar Mata Pelajaran Fikih Materi Adzan dan Iqomah dengan - Syaikhu, Ach; Ghina, Nabila Nilna; Istiqomah, Dewi (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
The use of instructional media significantly influences the learning outcomes and motivation of each student. In the implementation of Islamic jurisprudence (fikih) learning at MI Baitul Makmur Bangsalsari Jember, it was found that only some students were able to practice and read aloud the words of the call to prayer (adzan) and the call to commence prayer (iqomah). The purpose of implementing visual media is to enhance the spirit and motivation of the students in the MI Baitul Makmur Bangsalsari class. The method used in the application of this visual media is classroom action research, which involves describing real incidents that occur within the classroom. The results of this research indicate an increase in the enthusiasm and motivation of the students in the 2nd grade of MI Baitul Makmur Bangsalsari, as evidenced by their active participation in the classroom, such as confidently stepping forward to practice reciting the adzan and iqomah and reading and writing the Quran.